EFEKTIVITAS PENGGUNAAN DANA DESA UNTUK PENGEMBANGAN BUMDES TERHADAP PEREKONOMIAN LOKAL DESA MARINDAL II KECAMATAN PATUMBAK - Eshaulin Br Sembiring; Ameliya Harahap; Shelly Elprida Gajahmanik; Tifany Laura Balqis; Halking (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze and describe the impact of Village Fund utilization in the development of Village-Owned Enterprises (BUMDes) on the local economy in Marindal II Village, Patumbak District. The Village Fund policy is expected to encourage village independence by strengthening local economic institutions such as BUMDes. However, the effectiveness of its utilization in creating a tangible economic impact for the community still requires further research. This study uses a qualitative approach with descriptive methods. Research subjects were determined by purposive sampling, consisting of village government officials, BUMDes administrators, as well as community leaders and residents. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation studies. The collected data were then analyzed using the Miles and Huberman interactive analysis model that includes data reduction, data presentation, and conclusion drawing. The results of this study are expected to provide a clear picture of the contribution of BUMDes supported by Village Funds to the local economy and identify challenges faced in its management, so that it can serve as evaluation material for the village government and related stakeholders. Limited human resources and business management are the main obstacles so that the economic impact has not been felt optimally. The role of BUMDes is more dominant in service than in increasing community income.